HISTORICAL DEVELOPMENT OF THE ENTRY OF ISLAM IN EUROPE - Adissa Rahmasari (CV. Fahr Publishing, 2023)
This study aims to: (1) explain how the history of the entry of Islam in Europe, (2) analyze the transmission of knowledge to Europe and (3) analyzes the influence of Islamic civilization in Europe. The results of this study indicate that (1) Spain is the main place for the spread of Islam in Europe, (2) in transmission there are places and processes that influence Western thought and science by Islamic thought and science, namely: Andalusia, Sicily, the Crusades, (3) The influence of Islamic civilization has an important role in various fields, one of which is the field of Science. The influence of Islamic Civilization on the Western World can be divided into two types, namely Natural Sciences and Social Sciences.